Clinical Response to Tocilizumab in Severe Thyroid Eye Disease. Issue 3 (May 2017) - Sy, Aileen; Eliasieh, Kasra; Silkiss, Rona Z.
Abstract : Tocilizumab, in a preliminary study, was reported to be an effective therapy for moderate to severe thyroid eye disease. The authors describe the clinical response of 2 severe thyroid eye disease cases refractory to intravenous steroids and orbital decompression. Both patients demonstrated improved clinical activity scores with minimal side effects after tocilizumab therapy. In addition, post tocilizumab orbital fat biopsies demonstrated benign adipose tissue without evidence of inflammatory cells. Abstract : Tocilizumab appears to be an effective therapy for severe refractory thyroid eye disease. Histopathology post treatment reveals a paucity of inflammatory aggregates in orbital fat.